Pengaruh Sektor Pariwisata Alam terhadap Pertumbuhan Ekonomi di Sumatera Utara tahun 2012- 2022 - Penus Leonard Roningsih Sinurat; Vidia Wardana; Vingky Dwi Pratama; Bonaraja Purba; Nur Sakinah (Economic Reviews Journal, 2024)
This study looks at how the natural tourism industry in North Sumatra has influenced the region's economic growth between 2012 and 2022. Based on secondary data assessed using a simple linear regression approach, this research concludes that the natural tourism industry has had a significant and beneficial impact on local economic growth. Research findings show that any growth in the natural tourism industry will significantly increase North Sumatra's Gross Regional Domestic Product (GRDP). In addition, this research found that one of the main drivers of job creation and income growth for local communities is the nature tourism industry.